The Effect of Using Dynamic Mathematics Software on Students’ Understanding of the Geometric Meaning of the Derivative Concept - Erdem Çekmez, Adnan Baki (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
This study aimed to investigate the impact of dynamic mathematics software on students’ understanding of the geometric meaning of the concept of derivative at a single point. The participants consisted of students who were enrolled in two separate classes in a primary mathematics teacher education programme at a state university. The study adopted a quasi-experimental approach, with the two classes randomly assigned as a control and an experimental group. The instructional approach in the control group was traditional, whereas in the experimental group, computer-supported worksheets were used. The data were gathered through two tests that were developed by the researchers, as well as through clinical interviews conducted with selected students. One of the tests aimed to determine the level of knowledge of students about the concepts that are recognized in the literature as being crucial to the learning of the derivative concept by research reports; the other aimed to assess students’ learning regarding the content that was the focus of the study. Their performance was assessed using a rubric that was developed according to the level of understanding demonstrated in the students’ responses. A one-way analysis of covariance test was conducted on the students’ test scores to compare the performance of the two groups. The test concluded that there was a significant difference between the groups in favor of the experimental group. The clinical interviews showed that the students in the experimental group achieved a higher level of understanding, as proposed by APOS theory, in comparison to control group.